A historical narrative on pandemic Patterns of behavior and belief. (30th March 2022) - Khan, Gazala; Parwez, Sazzad
Abstract : Given the fractured reality of pandemic, the people's history needs to be written and understood. This paper provides a historical narrative on pandemics based on a literature review and makes inferences from the past and present. This narrative also reflects the ongoing COVID-19 pandemic in the world and India. The narratives provide a novel perspective to understand public health practices in a global context. It suggests the need for a more synchronized health response in pandemics while highlighting the uncertainties and challenges of using historical diseases as comparisons for the COVID-19 pandemic. The emphasis is on learning from historical evidence and ascertaining how these retrospective diagnoses help make arguments about health and illness in our present moment.